Magnetic and dielectric measurements of Mn substituted LaFeO3 compounds - Vansutre, Sandeep; Das, P.K.; Muthurajan, H.; Radha, S.; Basavaiah, N. (My University, 2014)
LaFeO3 is a known orthoferrite which shows multiferroic behaviour and magnetoelectric coupling at room temperature. In the present report we present our data of magnetic and dielectric measurem ents in Mn substituted LaFeO3. Samples are prepared using solid state reaction. Weak ferromagnetic behaviour is observed in samples for LaFeO3 and LaFe0.75 Mn0.25 O3 with orthorhombic structure. Higher Mnconcentration(x>0.5) indicate rhombohe dral structure and subsequently antiferromagnetic behaviour. Dielectric measurements show that for LaFe0.25 Mn0.75O3, dielectric constant has value of order 50 ×104and loss factor value is of order 50000, whereas for LaFe 0.75 Mn0.25O3.13, the same are 1.15×107 and 1400 respectively. The loss factor of these order indicate a leakage phenomenon.
Keywords: Magnetoelectric coupling; Magnetic measurements; LaFeO3